Strong electronic coupling and electron transfer in a Ce2@: I h-C80-H2P electron donor acceptor conjugate - Rudolf, Marc; Feng, Lai; Slanina, Zdenek; Wang, Weiwei; Nagase, Shigeru; Akasaka, Takeshi; Guldi, Dirk Michael (Nanoscale, 2016)
A newly designed electron donor-acceptor conjugate, namely Ce2@Ih-C80-H2P consisting of an endohedral dimetallofullerene Ce2@Ih-C80 and a free-base prophyrin (H2P), has been synthesized and systematically investigated. Basic characterization by means of NMR spectroscopy, steady-state absorption spectroscopy, and electrochemistry points to a folded configuration with sizeable interactions between Ce2@Ih-C80 and H2P. Complementary DFT optimization also results in the same conclusions. Time-resolved absorption spectroscopic investigations corroborate the formation of the (Ce2)-@Ih-C80-(H2P)+ radical ion pair state in non-polar as well as polar media. Overall, the modus operandi is an ultrafast through-space electron transfer enabled by the folded configuration in the ground and excited state.
CRIS-Team Scopus Importer:2023-03-07